Overexpression of junctional adhesion molecule-A and EphB2 predicts poor survival in lung adenocarcinoma patients. Issue 2 (February 2017) - Zhao, Chen; Wang, Aili; Lu, Funian; Chen, Hongxia; Fu, Pin; Zhao, Xianda; Chen, Honglei
Junctional adhesion molecules are important components of tight junctions, and Eph/ephrin proteins constitute the largest family of receptor tyrosine kinases. Both junctional adhesion molecules and Eph/ephrin are involved in normal tissue development and cancer progression. However, the expression levels and clinical significances of junctional adhesion molecule-A, a member of junctional adhesion molecules, and EphB2, a member of Eph/ephrin family, in lung adenocarcinoma patients are unclear. Therefore, in this study, we aimed to identify the expression and prognostic values of junctional adhesion molecule-A and EphB2 in lung adenocarcinoma patients' cohort. In our study, 70 (55.6%) showed high expression of junctional adhesion molecule-A protein and 51 (40.5%) showed high expression of EphB2 protein in 126 lung adenocarcinoma tissues. Junctional adhesion molecule-A and EphB2 expressions were both significantly increased in tumor tissues compared with noncancerous lung tissues. Kaplan–Meier analysis and log-rank test indicated that low expression of junctional adhesion molecule-A and EphB2 proteins can predict better survival and low mortality rate of lung adenocarcinomas. In univariate analysis, high expression levels of junctional adhesion molecule-A and EphB2 were both found to be significantly correlated with poor overall survival of lung adenocarcinoma patients (hazard ratio = 1.791, 95% confidence interval = 1.041–3.084, p = 0.035; hazard ratio = 1.762, 95% confidence interval = 1.038–2.992, p = 0.036, respectively). The multivariate Cox proportional hazard model demonstrated that EphB2 expression is an independent prognosis parameter in lung adenocarcinoma patients (hazard ratio = 1.738, 95% confidence interval = 1.023–2.952, p = 0.016). Taken together, high expression of junctional adhesion molecule-A and EphB2 can predict poor overall survival and high mortality rate, and EphB2 is an independent prognostic biomarker in lung adenocarcinoma patients.